Fetal Spinal Cord Transplants Support Growth of Supraspinal and Segmental Projections after Cervical Spinal Cord Hemisection in the Neonatal Rat - Diener, Pamela S. (J Neurosci, 1998)
Cervical spinal cord injury at birth permanently disrupts forelimb function in goal-directed reaching. Transplants of fetal spinal cord tissue permit the development of skilled forelimb use and associated postural adjustments (Diener and Bregman, 1998, companion article). The aim of this study was to determine whether transplants of fetal spinal cord tissue support the remodeling of supraspinal and segmental pathways that may underlie recovery of postural reflexes and forelimb movements. Although brainstem-spinal and segmental projections to the cervical spinal cord are present at birth, skilled forelimb reaching has not yet developed. Three-day-old rats received a cervical spinal cord overhemisection with or without transplantation of fetal spinal cord tissue (embryonic day 14); unoperated pups served as normal controls. Neuroanatomical tracing techniques were used to examine the organization of CNS pathways that may influence target-directed reaching. In animals with hemisections only, corticospinal, brainstem-spinal, and dorsal root projections within the spinal cord were decreased in number and extent. In contrast, animals receiving hemisections plus transplants exhibited growth of these projections throughout the transplant and over long distances within the host spinal cord caudal to the transplant. Raphespinal axons were apposed to numerous propriospinal neurons in control and transplant animals; these associations were greatly reduced in the lesion-only animals. These observations suggest that after neonatal cervical spinal cord injury, embryonic transplants support axonal growth of CNS pathways and specifically supraspinal input to propriospinal neurons. We suggest that after neonatal spinal injury in the rat, the transplant-mediated reestablishment of supraspinal input to spinal circuitry is the mechanism underlying the development of target-directed reaching and associated postural adjustments.